2016
DOI: 10.1080/13880209.2016.1233570
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of walnut ( Juglans regia ) prevents systemic hypertension induced by long-term use of dexamethasone: a promising strategy for steroid consumers

Abstract: Similar to captopril, walnut extract normalized dexamethasone-induced hypertension. A part of this beneficial effect apparently involves maintaining balance of the redox system and NO production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
(36 reference statements)
0
11
1
Order By: Relevance
“…Dexamethasone (DEX)‐induced hypertension has been shown by our group and others in both animals (Constantino et al, 2017; Dodic et al, 1999; Herrera et al, 2017; Herrera, Duchatsch, Tardelli, Dionisio, Santos, et al, 2020; Jesus et al, 2020; Joukar et al, 2017; Mondo et al, 2006; Ong et al, 2013) and humans (Anwar et al, 2016; Brotman et al, 2005; Williamson et al, 2015), but the effects of DEX on arterial stiffness are still unclear. This secondary type of hypertension has been associated with increased sympathetic nerve activity and impaired baroreflex activity (Constantino et al, 2017; Duchatsch et al, 2018; Fletcher et al, 2003; Herrera et al, 2016; Segar et al, 2006), oxidative stress (Joukar et al, 2017; Mondo et al, 2006; Schafer et al, 2005), increased renin angiotensin system activity (Forhead et al, 2000; Forhead et al, 2015; Hoshino et al, 1994; Suzuki et al, 1982) and skeletal muscle rarefaction (Herrera et al, 2016; Herrera et al, 2017; Herrera, Duchatsch, Tardelli, Dionisio, Shinohara, et al, 2020; Jesus et al, 2020). Preliminary results from our laboratory (data not published) have suggested that DEX‐induced hypertension was associated arterial stiffness, but the mechanisms are not totally clear.…”
Section: Introductionmentioning
confidence: 76%
“…Dexamethasone (DEX)‐induced hypertension has been shown by our group and others in both animals (Constantino et al, 2017; Dodic et al, 1999; Herrera et al, 2017; Herrera, Duchatsch, Tardelli, Dionisio, Santos, et al, 2020; Jesus et al, 2020; Joukar et al, 2017; Mondo et al, 2006; Ong et al, 2013) and humans (Anwar et al, 2016; Brotman et al, 2005; Williamson et al, 2015), but the effects of DEX on arterial stiffness are still unclear. This secondary type of hypertension has been associated with increased sympathetic nerve activity and impaired baroreflex activity (Constantino et al, 2017; Duchatsch et al, 2018; Fletcher et al, 2003; Herrera et al, 2016; Segar et al, 2006), oxidative stress (Joukar et al, 2017; Mondo et al, 2006; Schafer et al, 2005), increased renin angiotensin system activity (Forhead et al, 2000; Forhead et al, 2015; Hoshino et al, 1994; Suzuki et al, 1982) and skeletal muscle rarefaction (Herrera et al, 2016; Herrera et al, 2017; Herrera, Duchatsch, Tardelli, Dionisio, Shinohara, et al, 2020; Jesus et al, 2020). Preliminary results from our laboratory (data not published) have suggested that DEX‐induced hypertension was associated arterial stiffness, but the mechanisms are not totally clear.…”
Section: Introductionmentioning
confidence: 76%
“…Two-way ANOVA followed with post-hoc test did not confirm any significant effect of walnut diet on eNOS expression, in contrast to our expectations. Namely, walnuts contain considerable amounts of L-arginine, which is the precursor amino acid for NO biosynthesis (Xiao et al 2018) and improves serum NO level (Joukar et al 2017). The effects of LA and ALA, highly represented in walnut kernel, on endothelial cell functions and the related gene expression are influenced by LA/ALA ratios and their concentrations, and the mechanism may be partially mediated through NO/eNOS signalling pathways (Yang et al 2018).…”
Section: Protein Kinasesmentioning
confidence: 99%
“…In this context, some species of the Juglans genus exhibit diverse biological activities that may be helpful in the treatment of diseases such as diarrhea, helminthiasis, sinusitis, arthritis, stomach pain, fever, eczema, diabetes mellitus, skin disorders, asthma, hepatitis, liver fibrosis, dysfunctional thyroid, anorexia, urinary tract infection, and cancer [913]. The Juglans genus has been reported to have antihypertensive activity [1417] as well as antioxidant, lipolytic [18], antihyperglycemic, antilipidemic [19], neuronal cell-stimulating [20], and antiproliferative properties [21].…”
Section: Introductionmentioning
confidence: 99%